Have you written your will (WASIAT)? - Abdul Ghani, Roseziahazni; Abu Samah, A’tiqah Rashidah; Mohamad, Zuraida; Yusuf Ali, Noorhayati (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
Many Muslims consider writing a will to be a trivial matter in managing future estate planning. What's more, some of us consider conversations about Wills to be a Taboo matter because it deals with the question of death. So, it is not surprising if many Muslims do not prepare to write a will because they think it is not important as if praying for death. Hence the affairs of this property are placed under faraid only.